Evaluation of physical-spatial characteristics affecting the quality of apartment housing - Hessari, Pedram; Chegeni, Farhad (Journal of Architecture and Urbanism, 2024)
Housing quality is one of the most important domains of quality of life. One of the most important qualitative aspects of housing is paying attention to the residents’ satisfaction with their place of residence. The purpose of the upcoming research is to know the physical-spatial characteristics that affect the quality of apartment housing. The research method is combined and based on two quantitative and qualitative approaches. In this way, in the first part and the qualitative approach of the research, the text content analysis method was used. In this section, with the help of the content analysis method, the most important sources of the first category related to the quality of apartment housing are reviewed and the physical-spatial characteristics affecting the quality of the housing are identified. In the second stage of the research, with the help of a quantitative approach, the evaluation of people’s characteristics has been done with the help of TOPSIS method. The statistical population university professors related to housing was used to evaluate the physical-spatial characteristics. The findings of the research show that the characteristics related to housing quality are not only physical.